A true child of Papua New Guinea : memoir of a life in two worlds - Wilson, Maggie, 1953-2009 (McFarland & Company, Inc., Publishers, 2019)
"Maggie Wilson was born in the highlands of Papua New Guinea. Wilson's life serves as a window into the social and cultural transformations during the early years of the Australian administration in Papua New Guinea. Started as an autobiography and completed by Rosita Henry after Wilson's death, this ethnography tells her story and about lives she touched"--